Order and transcendence in Ecuador: the concepts of order from the Bourbon reforms to the Catholic Republic, 1748-1875. - Espinosa Fernández de Córdova, Carlos Ramiro (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article explores the trajectory of the concept of order in Ecuador, from the time of the Bourbon reforms to the confessional regime of Gabriel García Moreno (1860-1875). As a result of this study, three meanings of the term "order" were found: a stable and predictable ordering, a specific social order and the use of force against collective violence. Following Hilda Sábato and Carole Leal[1], a transition is explored from a transcendent socio-political order with divine approval and inserted into a hierarchical cosmos to an order that is the product of human will. Nevertheless, it is argued that this transition that took place in Ecuador was not linear, given that the regime of Gabriel García Moreno (1861-1865 and 1869-1875) employed a republican version of the transcendental social order in the second half of the 19th century. In theoretical-methodological terms, the article is based on conceptual history to diachronically trace the notion of order. The sources used to survey the transformations of the concept of order include newspapers, legal treaties and constitutional texts. The trajectory of the concept of order in Ecuador helps to understand the chronological and ideological peculiarities of the transition to political modernity in Ecuador and Latin America.